Pembangunan Pariwisata Berkelanjutan Oleh Dinas Kebudayaan Dan Pariwisata Kota Tanjungpinang (Studi Tanjung Siambang) - Restina Safitri; Rumzi Samin; Edy Akhyary (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Sustainable tourism development is a form of tourist satisfaction and an area is used as a tourist destination to increase business opportunities in the future. With tourism development to be able to benefit the community's economy. But this is still something that needs to be considered because there is still a lack of promotion of tourist areas and still lack of public awareness about the use of existing resources in Tanjung Siambang. This study aims to determine sustainable tourism development in Tanjung Siambang Tanjungpinang City. This research uses a type of descriptive research with a research approach used, namely qualitative research. The theory used is using the theory of Sustainable Tourism Development. The results of this study show that: 1) The role of the Government in sustainable Tourism Development, namely providing facilities and accessibility, forming Tourism Awareness Groups (POKDARWIS), providing training, socialization, and interests from stakeholders. 2) The role of the community, by organizing activities in developing tourism and improving business premises and submitting proposals, organizing events and making pamphlets, brochures, and posters, and utilizing technology. Sustainable Tourism Development carried out in Tanjung Siambang has been developed, because of the participation of the Government and the community in managing existing tourism.